NEUROSCIENCE TECHNIQUES AND THE PRIMING PROCESSES SIGNIFICANCE TO NEUROMARKETING ADVERTISING - Lobna Ben Nasr (European Scientific Journal, ESJ, 2014)
Neuromarketing is an innovative field of research which challenges the classic marketing model that has failed to fully understand the customer’s cognitive and affective drives for the purchasing decision. This research seeks to explore the contribution of neuroscience techniques and findings as well as the priming processes to promote the efficiency of commercial advertising of consumer goods in modern society. The neuroscience techniques which are Functional Magnetic Resonance Imaging (fMRI), Steady State Topography (SST), galvanic skin response (GSR), Eye tracking, Magneto-encephalography (MEG) reveal the human brain activity or heart pulses when exposed to marketing messages to highlight the brain responses to the ads. The pre/post testing techniques assess the ads degree of engagement to influence the consumer’s brain. These techniques aim to unveil the subliminal drives behind the purchasing decisions and identify the extent to which the ad draws the consumer’s attention and affecting his emotion in order to better satisfy the his needs and boost the sales. Nevertheless, despite the scientific significance of neuroscience and the concision it offers about the consumer’s engagement, the neuroscience techniques are not tools of designing the ad itself. It is the role of the priming processes to provide the marketers with the necessary techniques to design effective ads. These processes are: brain stimuli and the deep metaphors. The main concern of this article is to pinpoint the complementarity of neuroscience techniques and the priming processes in shaping neuromarketing ads.